HUBUNGAN ANTARA FRAGMENTASI DNA SPERMA DAN VIABILITAS SPERMA PADA KASUS INFERTILITAS PRIA - , LAILATUSSAADAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Infertility affects 10-15% of the couples of reproductive age in the world. The male factor contributes 40-50% of infertility cases. WHO routine sperm analysis can provide a limited prediction of male fertility potential and is not always able to explain the cause of male infertility. In addition to assessing sperm viability, sperm DNA integrity test is important to be performed in infertile patients. Unfortunately, the correlation between both of them havenât been understood clearly. Objective : This study was made specifically to determine the relationship between sperm DNA fragmentation and sperm viability in the male infertility cases. In this study, seminal leukocyte also counted as the confounding variable. Methods : The study was performed using analytical observational with cross-sectional method. Subjects were 28 men with infertility complaints. Data were obtained from medical Record at Permata Hati Clinic, RSUP dr.Sardjito, Yogyakarta. Results : There was a negative correlation between sperm DNA fragmentation and sperm viability, where the bivariate analysis using Chi-square method showed a statistically significant result (P=0.02). Multivariate analysis using logistic regression also showed a significant associated result between sperm DNA fragmentation and sperm viability, even after the confounding variable was included, namely semen leukocyte count, the results obtained remained associated significantly (OR= 7.31